HUBUNGAN ANTARA IMPLEMENTASI KEBIJAKAN PERENCANAAN PEMBELAJARAN BERPERSPEKTIF GENDER DENGAN PRAKTIK KESETARAAN DI MTS SA MIFTAHUL FALAH - Suhertini, Heni; Nugraha, Mulyawan Safwandy (Epistemic: Jurnal Ilmiah Pendidikan, 2026)
Gender equity in education is not merely determined by policies but by how they are translated into classroom practices. Gender-responsive lesson planning is a strategic policy instrument for fostering equitable and inclusive learning in madrasah education. This study aims to analyze the implementation of gender-responsive lesson planning, the practice of gender equity in classroom learning, and the relationship between both. A quantitative approach with a correlational design was employed. Data were collected through standardized questionnaires administered to teachers and students, then analyzed using descriptive and inferential statistical techniques. The findings indicate that the implementation of gender-responsive lesson planning is at a high level, while gender equity practices are consistently applied. Correlational analysis reveals a strong and significant positive relationship between the quality of lesson planning and the realization of gender equity in classroom practices (r = 0.78, p < 0.05). These results suggest that well-designed, gender-responsive lesson planning plays a crucial role in promoting educational equity. The study implies that strengthening policy-oriented lesson planning, supported by institutional commitment and continuous teacher capacity development, is essential for creating inclusive and gender-equitable learning environments in madrasah education